Family Firm Configurations for High Performance: The Role of Entrepreneurship and Ambidexterity. (6th December 2017) - Hughes, Mathew; Filser, Matthias; Harms, Rainer; Kraus, Sascha; Chang, Man‐Ling; Cheng, Cheng‐Feng
Abstract: The performance drivers of family firms have spawned considerable research interest. Almost exclusively this research has relied on independent sets of explanatory variables in linear analyses. These analyses mask the complex interdependencies that are likely to exist among key success factors, leading to faulty theory and misspecified implications for practice. As treatment, the authors propose a configuration approach to family firm performance that accounts for complex interdependencies among entrepreneurial, innovation and family influence conditions. Using a fuzzy set qualitative comparative analysis of a sample of 129 Finnish family firms, the authors identify sufficient conditions with regard to the existence or absence of antecedent conditions to family firm performance. These conditions include entrepreneurial orientation, exploration and exploitation activities that form causal paths towards family firm performance. To enrich the analysis, the authors theorize and empirically analyse how these conditions might differ in family firms with high and low levels of family influence. They deepen the current understanding of configurations that promote the performance of family firms, offer important implications for theory and practice, and set new directions for future research on the strategic management of family firms. The results are also virtually identical and insensitive to change across subjective and objective performance measures.